2012
DOI: 10.1590/s1519-69842012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of herbicides on Escherichia coli growth

Abstract: Agriculture uses a huge variety and quantity of chemicals. If, on one hand, the goal is to increase productivity, on the other hand these products contaminate aquatic environments. Among these products, herbicides deserve greater attention in relation to contamination of aquatic environments due to their extensive use to weed control. This study was carried out because the effects of these molecules on aquatic microorganisms such as Escherichia coli, is still unclear. Using microdilution plate assays, Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
(22 reference statements)
1
9
0
1
Order By: Relevance
“…Strain Ros2 gave results 90 mg g -1 without stress and 110 mg g -1 with stress. Use of pesticides help in causing bacteriostatic effect on microorganisms (Botelho et al, 2012). According to the study, the maximum toxicity by pesticide pyriproxyfen was observed to nodule numbers in pea, root and shoot dry biomass, shoot nitrogen and root phosphorus in greengram, leghaemoglobin, seed protein and chlorophyll content in chickpea.…”
Section: Discussionmentioning
confidence: 95%
“…Strain Ros2 gave results 90 mg g -1 without stress and 110 mg g -1 with stress. Use of pesticides help in causing bacteriostatic effect on microorganisms (Botelho et al, 2012). According to the study, the maximum toxicity by pesticide pyriproxyfen was observed to nodule numbers in pea, root and shoot dry biomass, shoot nitrogen and root phosphorus in greengram, leghaemoglobin, seed protein and chlorophyll content in chickpea.…”
Section: Discussionmentioning
confidence: 95%
“…Toxicity of glyphosate to bacteria and other microorganisms have been reported (Botelho, et al, 2012;Shehata et al, 2013, Nweke et al, 2014. Glyphosate exhibits higher toxicity in soil-free media (Busse et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro evaluation of the toxic effects of herbicides revealed a negative effect on the growth of strains of E. coli , particularly at higher doses [34], and also served as a model for the identification of genes and enzymatic activities involved in the antioxidant system in general [48][50]. Until this date, there are no studies involving herbicides degrading ability by non-environmental strains as E. coli DH5-α.…”
Section: Resultsmentioning
confidence: 99%
“…Botelho et al [34] analyzed many widely used commercial formulations of herbicides, and only paraquat decreased the growth of the E. coli ATCC 25922 strain. In the present study, field doses (1×) of mesotrione, which is considered less toxic than the commercial herbicide [22], decreased the viability of E. coli DH5-α within 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation